147th Meeting of the Institute - More Than 2100 People, a New Record, Renew Old Friendship and Discuss 200 Papers - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
CERTAINLY in point of attendance, and doubtless in several other ways as well, the 147th meeting of the A.I.M.E. was the best ever held. In times of depression, mining engineers and metallurgists have plenty of time to come to the Annual Meeting but money is scarce; at the height of industrial activity they have plenty of money but no time. "The current period of transition seemed to provide ideal conditions for' both the preparation of papers and attendance at their presentation. The weather made even the Californians present envious though the weather man gets no credit, for rain and snow was what he willed. Among the elevator men, the miners have the reputation of being the toughest crowd to handle, though the best natured, withal, of all the engineering groups that meet in the Engineering Societies Building. This year Your inquiring reporter was told, "it was the damnedest meeting I ever saw; they